Hubungan Pola Makan Dengan Tingkatan Hipertensi Pada Penderita HipertensiDi Poli Penyakit Dalam Rsi Sakinah Mojokerto - Achwandi, S.Kcp. Ns., M.Kc, Moch.; S.Kcp. Ns M.Kcs & Nurlailiyati, ArifWicaksono (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractHypertension is a condition where there is an increasein blood pressure over than 40/90 mmHg. Unhealthy eating diet, like a lot of foods high in salt, fat, low in fiber, with the diet is exposed to higher risk of hypertension. The research purposes to determine the relationship of diet and level of hypertension in patients with hypertension. The research design was analytic correlational with cross sectional approach. The research population was all patients with hypertension in internal Illness poly RSI Sakinah on 15th-18th June 2016. Samples were taken with consecutive sampling technique that fulfilled the inclusion criteria as much as 35 respondents. The research variables are diet as independent variables and hypertension levels as the dependent variable. The instruments used questionnaires to assess dietary and blood pressures observation to assess the level of hypertension, then analyze the data in Spearman rho test and presented in the form of frequencytables. The results showed a total of 35 respondents, that the 15 respondents with a healthy diet mostly had mild hypertension category were 12 respondents (65,7%). While 20 respondents with unhealthy eating patterns mostly had hypertension with middle category as much as 9 respondents (48,2%). The results of analysis by Spearman rho test data is obtained p 0.012 and the value of a 0.05, so that the conclusions drawn p <a is 0.012 <0.05 then HO is rejected, which means there is a relationship diet with levels of hypertension in patients with hypertension. The research results showed that diet can influence the occurrence of hypertension, where a healthy diet then one will be spared from hypertension and vice versa.Keywords:Prayer Humility, Blood Pressure, Hypertension